Penentuan Kadar Etanol Dan Asam Laktat Dari Hasil Fermentasi Susu Kefir Kambing - Annisa Utami; Anny Sartika Daulay; Ridwanto Ridwanto; Ainil Fithri Pulungan (Journal of Pharmaceutical and Sciences, 2026)
Goat-milk kefir contains lactic acid and ethanol formed through the symbiotic metabolism of lactic acid bacteria and yeasts; however, information on their changes during prolonged fermentation remains limited. This study aimed to characterize ethanol accumulation during six days of goat-milk kefir fermentation and to determine lactic acid after 24 h. Goat milk (250 mL) was heated at 75 °C, inoculated with 4% (w/v) kefir grains, and fermented at 25 ± 2 °C. Ethanol was screened using iodoform, acidified potassium dichromate, and esterification reactions, followed by visible spectrophotometric quantification at 443 nm after Conway microdiffusion. Lactic acid was quantified using HPLC-UV at 210 nm with 50 mM phosphate buffer (pH 2.8), a flow rate of 1 mL/min, and an injection volume of 20 µL. The pH decreased from 4.19 on day 1 to 2.15 on day 6, while ethanol increased from 0.227 to 0.657 g/dL (p<0.001). Commercial kefir contained 0.453 g/dL ethanol. The ethanol and lactic-acid calibration models showed R² values of 0.996; lactic acid in 24-h kefir was 3.923%. Prolonged fermentation therefore produced progressive acidification accompanied by ethanol accumulation, with the greatest change occurring during the first three days. These findings establish fermentation time as an important determinant of the metabolite profile of goat-milk kefir and provide a basis for subsequent studies using independent fermentation batches and fully validated analytical methods.